2003
DOI: 10.1046/j.1475-097x.2003.00465.x
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous non‐invasive assessment of arterial stiffness and haemodynamics – a validation study

Abstract: The purpose of the study was to estimate the reliability of whole-body impedance cardiography (ICGWB)-derived pulse wave velocity (PWV) and stroke volume index to pulse pressure (SI/PP) measurements. The repeatability and reproducibility of ICGWB parameters were also determined. Agreement between the impedance and Doppler ultrasound-based PWV measurements was estimated in 25 healthy subjects in two consecutive measurements. Impedance-derived SI/PP (SIICG/PP) estimates were compared with simultaneously measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
72
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 90 publications
(76 citation statements)
references
References 14 publications
4
72
0
Order By: Relevance
“…A whole-body impedance cardiography device (CircMon; JR Medical Ltd) that records changes in body electrical impedance during cardiac cycles was used to determine heart rate, stroke volume, and cardiac output. 25,[33][34][35] The description of the method and electrode configuration was reported previously. 25,[33][34][35] The values were normalized to body surface area and expressed as cardiac index, stroke index, systemic vascular resistance index (SVRI), and left cardiac work index (LCWI).…”
Section: Hemodynamic Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…A whole-body impedance cardiography device (CircMon; JR Medical Ltd) that records changes in body electrical impedance during cardiac cycles was used to determine heart rate, stroke volume, and cardiac output. 25,[33][34][35] The description of the method and electrode configuration was reported previously. 25,[33][34][35] The values were normalized to body surface area and expressed as cardiac index, stroke index, systemic vascular resistance index (SVRI), and left cardiac work index (LCWI).…”
Section: Hemodynamic Measurementsmentioning
confidence: 99%
“…25,[33][34][35] The description of the method and electrode configuration was reported previously. 25,[33][34][35] The values were normalized to body surface area and expressed as cardiac index, stroke index, systemic vascular resistance index (SVRI), and left cardiac work index (LCWI). SVRI was calculated from the radial BP signal and cardiac index measured by the CircMon device.…”
Section: Hemodynamic Measurementsmentioning
confidence: 99%
“…The PWV is determined from the distance and the time difference between the two recording sites. A more detailed description of the method and the validation study has been reported previously (K€ o€ obi et al, 2003;Aatola et al, 2010). Measures of PWV have been found to possess both good repeatability and reproducibility (99% and 87%, respectively) (Tahvanainen et al, 2009).…”
Section: Pulse Wave Velocitymentioning
confidence: 99%
“…The CircMon device (JR Medical Ltd, Tallinn, Estonia) was used to determine heart rate (HR), stroke index (stroke volume/body surface area), cardiac index (cardiac output/body surface area), systemic vascular resistance index (SVRI), aortic to popliteal pulse wave velocity (PWV), and extracellular fluid volume. [16][17][18][19] The description and repeatability of the method have been published elsewhere. [16][17][18][19] SVRI was calculated from radial tonometric BP and cardiac index measured by the CircMon device.…”
Section: Whole-body Impedance Cardiographymentioning
confidence: 99%
“…[16][17][18][19] The description and repeatability of the method have been published elsewhere. [16][17][18][19] SVRI was calculated from radial tonometric BP and cardiac index measured by the CircMon device. With CircMon, cardiac output shows good agreement with the thermodilution method, 17 while stroke volume shows good correlation with values obtained using 3-dimensional ultrasound.…”
Section: Whole-body Impedance Cardiographymentioning
confidence: 99%